ISLAMSKI SVJETOPOGLED I MODERNA ZNANOST - Nasr, Seyyed Hossein; Fatić, Almir (Novi Muallim, 2022)
UDK 001.3:28 28-1 Prijevod s engleskog: Almir Fatić “The Islamic Worldview and Modern Science” (Keynote Address) u: Seyyed Hossein Nasr, In conversation with Muzaffar Iqbal, Islam, Science, Muslims and Technology (Kuala Lumpur:Islamic Book Trust, 2007), 177-203.